Comparison of accumulation and distribution of PEGylated and CD-47-functionalized magnetic nanoporous silica nanoparticles in an in vivo mouse model of implant infection - Heidi Harting; Timo Herrmann; Nina Ehlert; Jessica Meißner; Nina Angrisani; Janin Reifenrath (PLoS ONE, 2025)
Introduction Drug targeting using nanoparticles is a much-researched topic. Rapid interactions of nanoparticles with the host’s immune system and clearance from the circulation is a major problem resulting in non-satisfying accumulation rates in the desired region. The aim of the presented study was to compare organ distribution and implant accumulation of magnetic nanoporous silica nanoparticles (MNPSNP) functionalized with either Polyethylenglycol (PEG) or CD-47 in vivo in a mouse model of implant infection. Methods Synthesis and functionalization of the magnetic core-shell nanoparticles is described. In the in vivo study, 32 mice were included and received an in staphylococcus aureus solution preincubated magnetic implant subcutaneously on the left and a nonmagnetic implant on the right hind leg. MNPSNP accumulation in the inner organs as well as on and around the implants was analyzed in dependence on the functionalization. Results MNPSNP were successfully functionalized with PEG or CD-47. In vivo, unexpectedly both nanoparticle variants accumulated mainly in liver and spleen. In the tissue, surrounding the implants higher nanoparticle accumulation was seen in areas with more severe signs of inflammation Nanoparticles were detectable on both implant materials, but accumulation rate was very low. Conclusion Although various literature describes higher accumulation rates for nanoparticles functionalized with CD-47 in target areas and a reduced accumulation in liver and spleen, this could not be shown within this study. Possible instability or rapid agglomeration of the particles are conceivable reasons. Higher accumulation rates in areas with more severe signs of inflammation indicate that inflammatory cells might be essential for the delivery of nanoparticles into inflamed regions.